Structures of Oppression or Inclusion: What Systemic Factors Impact Inclusion in Disability and Rehabilitation Research? - Layton, Natasha; Martin, Rachelle; Bourke, John; Kayes, NM (MDPI AG, 2024)
This manuscript considers the drivers towards inclusive research in the field of disability and rehabilitation; including some of the tools and frameworks that may support its realisation. We, a group of researchers engaged in rehabilitation research from lived experience and ‘conventional’ (non-lived experience) positions, reflect on our collective endeavours to bring about inclusion in research and specify the systemic factors constraining inclusion in research. We conclude by asking the following: how might we reimagine systems where the mechanisms of research production are in the hands of those impacted by the research, and where are intersectionalities both sought and valued?
Keywords: 16 Studies in Human Society; 18 Law and Legal Studies; 44 Human society; 48 Law and legal studies; inclusive; disability; rehabilitation; research